Edible Allium L. species that are sold as fresh vegetables in public bazaars of Hakkâri province and its surroundings in Turkey - Fırat, Mehmet; Azırat, Akın (Erdoğan ÇİÇEK, 2016)
The material of this study comprises observations of 9 Allium L. species between 1999 and 2014 which are sold in public bazaars of Hakkâri province; Yüksekova, Şemdinli and Çukurca districts, and Derecik town in Spring, and of the floristic field surveys in and around Hakkari which is located in the C9, C10 squares according to the grid square system in the Flora of Turkey. Green leaves of these species are sold in the markets of the region commonly, which are; Allium akaka S. G. Gmel. ex Schult. & Schult., Allium calocephalum Wendelbo, Allium noeanum Reut. ex Regel, Allium rhetoreanum Nab., Allium schoenoprasum L., Allium shatakiense Rech. f., Allium szovitsii Regel, Allium vineale L., Allium scorodoprasum L. subsp. rotundum (L.) Stearn. This study provides information about the natural habitats of the 9 species of the genus Allium in Turkey, and gives information with photos about how they are collected, dried, marketed, and used in detail.